cGAS deficiency enhances inflammasome activation in macrophages and inflammatory pathology in pristane-induced lupus - Kumpunya, Sarinya; Thim-uam, Arthid; Thumarat, Chisanu; Leelahavanichkul, Asada; Kalpongnukul, Nuttiya; Chantaravisoot, Naphat; Pisitkun, Trairak; Pisitkun, Prapaporn (Frontiers in Immunology, 2022)
Type I interferon (IFN) plays a vital role in the pathogenesis of systemic lupus erythematosus. Cyclic GMP-AMP synthase (cGAS) is a cytosolic DNA sensor that recognizes dsDNA and creates cGAMP to activate STING-mediated type I IFN production. The activation of STING induces lupus disease in Fcgr2b-deficient mice through the differentiation of dendritic cells. In contrast, Cgas-deficient mice could be generated more autoantibody production and proteinuria in pristane-induced lupus (PIL). These data suggested that the other dsDNA sensors could be involved in lupus development mechanisms. This study aimed to identify the cGAS-mediated mechanisms contributing to lupus pathogenesis in PIL. The Cgas-/- mice developed more severe pulmonary hemorrhage and autoantibody production than WT mice. The activated dendritic cells, IFN-g-, and IL-17a-producing T helper cells, and infiltrated macrophages in the lung were detected in Cgas-/- mice higher than in WT mice. We observed an increase in expression of Aim2, Casp11, and Ifi16 in the lung and serum IL-1α but IL-1β in pristane-injected Cgas-/- mice. The rise of Caspase-11 in the lung of pristane-injected Cgas-/- mice suggested noncanonical inflammasome activation. The activation of AIM2 and NLRP3 inflammasomes in bone marrow-derived macrophages (BMDMs) enhanced the number of dead cells in Cgas-/- mice compared with WT mice. Activation of the inflammasome significantly induced pyroptosis in Cgas-/- BMDMs. The dsDNA level, but not mitochondrial DNA, increased dramatically in pristane-injected Cgas-/- mice suggesting the dsDNA could be a ligand activating inflammasomes. The cGAS agonist-induced BMDM activation in the Cgas-/- mice indicated that the activation of DNA sensors other than cGAS enhanced activated macrophages. These findings suggested that cGAS hampers the unusual noncanonical inflammasome activation through other DNA sensors.